Psychometric properties of the Serbian version of Mental Toughness Inventory and Dark Triad Dirty Dozen in police students - Milošević, Miloš; Božović, Branislav; Dopsaj, Milivoj (NBP. Nauka, bezbednosti, policija, 2022)
The aim of this paper was to examine the psychometric properties of the Serbian translations Mental Toughness Inventory (MTI) and the Dark Triad Dirty Dozen (DTDD) in Population of Police Academy Cadets. The research was conducted on a sample of 82 students of 1st and 2st year in Criminal Police University. Considering the specificity of the sample both instruments showed good reliability (Cronbach’s Alpha Based on Standardized Item α=0.81 for MTI and α=0.84 for DDTD), factor structure is confirmed MTI (χ²=51.5, p<0.001, CFI=0.864 for MTI and χ²=105, p<0.001, CFI=0.886 for DTDD) as well as convergent (r=-.384, p<0.01 between Mental toughness, and Machiavellianism) and discriminant validity. Space for further research of this topic but as well as space for the usage of the instruments in the existing system for selecting candidates for police work has been described.